2020
DOI: 10.1108/srj-09-2018-0230
|View full text |Cite
|
Sign up to set email alerts
|

CSR narrative under Islamic banking paradigm

Abstract: Purpose This paper aims to understand corporate social responsibility (CSR) narrative under the Islamic banking paradigm by three aspects, narrative review of the literature, review of the definitions of CSR and review of factors that cause divergence from conventional percepts. Design/methodology/approach This is a theoretical paper based on literature and aims to understand the CSR narrative under the paradigm of Islamic banking. Findings Religion brings new dimensions of ethics and expands the scope of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 41 publications
0
17
0
1
Order By: Relevance
“…Muhammad Azam, Muhammed Usman Khalid and Syeda Zinnaira Zia [16] [17], conducted a study of sharia principles compliance on social performance (ISR) whose results concluded that sharia compliance affects social performance (ISR), these results are not in line with research by Roshima Said [18] which concludes that sharia compliance has no effect on Islamic social responsibility.…”
Section: Introductionmentioning
confidence: 89%
“…Muhammad Azam, Muhammed Usman Khalid and Syeda Zinnaira Zia [16] [17], conducted a study of sharia principles compliance on social performance (ISR) whose results concluded that sharia compliance affects social performance (ISR), these results are not in line with research by Roshima Said [18] which concludes that sharia compliance has no effect on Islamic social responsibility.…”
Section: Introductionmentioning
confidence: 89%
“…Islamic banking represents a new wave of corporations whose social goals are as important as generating profit (Zafar & Sulaiman, 2019). Jouti (2019) used a theoretical approach in building sustainable ecosystems through existing social initiatives and practices.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Carroll (1979) menjelaskan bahwa CSR adalah tanggungjawab sosial perusahaan yang mencakup ekspektasi ekonomi, hukum, etika dan kebijaksanaan atau filantropi yang dimiliki masyarakat terhadap perusahaan pada suatu waktu tertentu. Dalam perbankan syariah dimana aktivitas usahanya berlandaskan doktrin hukum Islam, konsep CSR harus dieksplorasi dengan lensa prinsipprinsip dan nilai-nilai Islam agar sesuai dengan paradigma perbankan syariah (Zafar & Sulaiman, 2019). Khurshid et al (2014) berdasarkan teori CSR Carroll, memberikan konsep CSR berdasarkan syariah atau disebut Islamic CSR sehingga menghasilkan definisi bahwa Islamic CSR adalah tanggungjawab sosial perusahaan untuk memenuhi ekspektasi stakeholder terkait implementasi nilai-nilai syariah pada ekonomi, hukum, etika dan kebijaksanaan atau filantropi.…”
Section: Landasan Teori Dan Pengembangan Hipotesisunclassified